Exploration of Natural Dye Plants in Kumpang Ilong Village, Belitang Hulu District, Sekadau Regency - Listiani, Etma; Masriani, Masriani; Erlina, Erlina (Universitas Pendidikan Mandalika, 2024)
The people of Kumpang Ilong Village, Belitang Hulu District, Sekadau Regency have used plants as natural dyes for daily needs, such as dyes for woven fabrics, food, and beverages. The use of natural dyes from local plants can be an environmentally friendly alternative compared to synthetic dyes which can cause various problems such as environmental pollution, toxicity, and the risk of allergies to humans. This study aims to identify the types, parts, and ways of using plants as natural dyes by the community of Kumpang Ilong village, Belitang Hulu District, Sekadau Regency. This study is a descriptive research to describe the use of plants used as natural dyes by the people of Kumpang Ilong Village using a data collection method that is carried out in a triangulation manner with interview, observation, and documentation techniques. The determination of 24 informants was carried out by purposive sampling technique in order to obtain detailed information. Information was obtained by direct observation using semi-structured interview techniques. The results of the study showed that there were 20 types of natural dye plants used by the people of Kumpang Ilong village, Belitang Hulu District, Sekadau Regency.